A Review on Kharbuja Rasala: A Traditional Ayurvedic Functional Dairy Product - Yadav, Garima; Arvind, Dr.; Chowdhury, Dr. Kanchan (South Eastern European Journal of Public Health, 2025)
Rasala is a traditional Ayurvedic recipe mentioned in Ayurvedic classical books, also known as ‘Shikharini’ in Sanskrit. Various Acharya have mentioned that it is a summer preparation made with curd. It is nutritive, apphrodisiac, unctous, provides strength and is tasty. Kharbuja Rasala is a form of Rasala, mentioned in “Kshemkutuhalam” by Acharya Kshemraj Sharma. Kharbuja Rasala is a traditional (Ayurvedic) recipe that is also known as “Medicated Curd”. This recipe is a combination of many ingredients, each of which has a distinct rasa with healing properties. In modern terms, it is a functional dairy product with numerous medicinal characteristics. It provides the body strength and nourishment. So far, dairy products have been at the core of functional food development, and the development of such health-promoting functional dairy products has increased in the dairy sector and gaining popularity these days. One of the reasons for the formation of this preparation is consumer awareness of their personal health. The purpose of the study is to emphasise the traditional dairy product Rasala as well as Kharbuja Rasala and its health-promoting properties. The purpose of the study is to emphasise the traditional dairy product Rasala as well as Kharbuja Rasala as mentioned in Ayurvedic classical text book and its medicinal qualities as functional food. This review paper has been written with the help of Ayurvedic classical text books, and related modern as well as Ayurvedic research papers.